Oral prodrug of remdesivir parent GS-441524 is efficacious against SARS-CoV-2 in ferrets - Robert M. Cox (Nature Portfolio, 2021)
Remdesivir is an approved antiviral treatment for COVID-19, but it needs to be administered intravenously. Here, Cox et al. show that GS-621763, a prodrug of remdesivir parent nucleoside GS-441524 has good oral bioavailability and inhibits SARS-CoV-2 and variants of concerns in ferrets.